Combined Autologous Chondrocyte and Bone Marrow Mesenchymal Stromal Cell Implantation in the Knee: An 8-year Follow Up of Two First-In-Man Cases. Issue 7 (July 2019) - Wang, Jingsong; Wright, Karina T.; Perry, Jade; Tins, Bernhard; Hopkins, Timothy; Hulme, Charlotte; McCarthy, Helen S.; Brown, Ashley; Richardson, James B.
Autologous chondrocyte implantation (ACI) has been used to treat cartilage defects for >20 years, with promising clinical outcomes. Here, we report two first-in-man cases (patient A and B) treated with combined autologous chondrocyte and bone marrow mesenchymal stromal cell implantation (CACAMI), with 8-year follow up. Two patients with International Cartilage Repair Society (ICRS) grade III–IV cartilage lesions underwent a co-implantation of autologous chondrocytes and bone marrow-derived mesenchymal stromal cells (BM-MSCs) between February 2008 and October 2009. In brief, chondrocytes and BM-MSCs were separately isolated and culture-expanded in a good manufacturing practice laboratory for a period of 2–4 weeks. Cells were then implanted in combination into cartilage defects and patients were clinically evaluated preoperatively and postoperatively, using the self-reported Lysholm knee score and magnetic resonance imaging (MRI). Postoperative Lysholm scores were compared with the Oswestry risk of knee arthroplasty (ORKA) scores. Patient A also had a second-look arthroscopy, at which time a biopsy of the repair site was taken. Both patients demonstrated a significant long-term improvement in knee function, with postoperative Lysholm scores being consistently higher than ORKA predictions. The most recent Lysholm scores, 8 years after surgery were 100/100 (Patient A) and 88/100 (Patient B), where 100 represents a fully functioning knee joint. Bone marrow lesion (BML) volume was shown to decrease on postoperative MRIs in both patients. Cartilage defect area increased in patient A, but declined initially for patient B, slightly increasing again 2 years after treatment. The repair site biopsy taken from patient A at 14 months postoperatively, demonstrated a thin layer of fibrocartilage covering the treated defect site. The use of a combination of cultured autologous chondrocytes and BM-MSCs appears to confer long-term benefit in this two-patient case study. Improvements in knee function perhaps relate to the observed reduction in the size of the BML.